Uporaba novega L1 RTK GNSS sprejemnika na primeru alpskega smučanja - Krejač, Klemen (Šport (Ljubljana), 2021)
Nowadays we hardly notice the daily use of navigation systems. The Global Navigation Satellite System (GNSS) is being integrated into many electronic devices and its operation is not distracting. In sports, it is popularly used especially for monitoring and analyzing training sessions and competitions. In the European area, the most widely used systems are the American GPS and the Russian GLONASS, and the most effective is the simultaneous use of both. As the technology develops, the receivers are becoming smaller and lighter, and therefore less intrusive in use. In the measurement of alpine skiing, we used the newly developed singlefrequency »Real-Time Kinematic« (L1 RTK) GNSS system, which enhances the accuracy of the receiver (rover) in real time using corrections from the reference (base) station. Using the data obtained in this way, we can accurately analyse the trajectory and speed of the skier. Such a system achieves a high accuracy in practice, in most cases between 3 and 8 cm horizontally and between 6 and 13 cm vertically.
Keywords: alpine skiing; alpsko smučanje; case study; GLONASS; GNSS; GNSS reciver; GPS; IKT; L1 RTK; natančnost; precision; sodobna tehnologija; sport; sprejemnik GNSS; šport; študija primera; technology